1976
DOI: 10.1007/bf00286851
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that chromosome band 22q12 is concerned with cell proliferation in chronic myeloid leukaemia

Abstract: A man and two of his three children carried an abnormally short chromosome 22 resembling the Philadelphia chromosome (Ph1). Giemsa banding showed that the abnormal chromosome resulted from a translocation t(11;22) (q25;q13). The breakpoint on chromosome 22 was at the q12/q13 band interface compared with the breakpoint of Ph1 at the q11/q12 band interface. The absence of leukaemia or haematological disorder in members of this family suggests that the critical genetic site on chromosome 22 concerned with abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1977
1977
1981
1981

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…The further finding of a Phi-like chromosome in a few cells from 1M patients is not altogether surprising. A similar chromosome has been reported in several myeloproliferative diseases other than CML (Sandberg et al 1971), in some asymptomatic individuals (as in the case of Bikini fishermen after exposure to fall-out radiation (Makino 1975)), and as familial markers (Fitzgerald 1976(Fitzgerald , F u et al 1976. In some such instances, C-group chromosomes were recognised as recipients of the translocated material, but in this study no recipient chromosome could be identified.…”
Section: Discussionsupporting
confidence: 58%
“…The further finding of a Phi-like chromosome in a few cells from 1M patients is not altogether surprising. A similar chromosome has been reported in several myeloproliferative diseases other than CML (Sandberg et al 1971), in some asymptomatic individuals (as in the case of Bikini fishermen after exposure to fall-out radiation (Makino 1975)), and as familial markers (Fitzgerald 1976(Fitzgerald , F u et al 1976. In some such instances, C-group chromosomes were recognised as recipients of the translocated material, but in this study no recipient chromosome could be identified.…”
Section: Discussionsupporting
confidence: 58%